Simulating a travel-related origin of Candida auris in New York–New Jersey - Rita R. Verma; Edward Kiegle; Alexander C. Keyel; Sudha Chaturvedi; Vishnu Chaturvedi (Microbiology Spectrum)
ABSTRACT Candida auris first appeared in the United States in 2013 in New York–New Jersey (NY-NJ) and led to an unprecedented outbreak since 2016. We hypothesized C. auris’ introduction to NY-NJ was not a random event but related to travel patterns between South Asia and NY-NJ. New York City is a US hub for international passengers, including those from South Asia. We tested the hypothesis by simulating introductions to NY-NJ with a Monte Carlo simulation based on travel from South Asia, proportion of US population in NY-NJ, proportion of hospitals in NY-NJ, and finally, proportion of all travelers entering the United States through NY-NJ. The C. auris outbreak occurred during increasing travel and trade, and South Asia travel routes predict the distribution of early C. auris cases in NY-NJ. The local mobility network within hospitals and extended stay healthcare facilities were also relevant in the spread of C. auris. Our observations and simulations link travel patterns to C. auris origin and spread and warrant further investigations for understanding the continued spread of the pathogen.IMPORTANCECandida auris is an emerging fungal pathogen, with resistance to several antifungal drugs. Serious C. auris infections affect hospitalized patients and residents of long-term care facilities, although the pathogen can also be present on a healthy individual’s skin. Many studies have shown international introductions of C. auris to the United States. Here, we present a simulation that supports the hypothesis that the earlier introductions of C. auris in the New York–New Jersey area are not random but related to travel networks.